2014
DOI: 10.1093/cid/ciu853
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Betaherpesvirus DNAemia in Children >3 Weeks and <2 Years of Age Admitted to a Large Referral Hospital in Sub-Saharan Africa

Abstract: Highly prevalent HCMV DNAemia was independently associated with HIV infection and being underweight across all age groups, and was also associated with meningitis, with previously underappreciated implications for the health and development of African children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 49 publications
4
52
0
4
Order By: Relevance
“…Several studies reported the prevalence of CMV viremia (cut‐off values ranging from 50 to 200 copies/mL) in different populations with no reported CMV disease symptoms. Detectable CMV DNA in blood in HIV‐infected individuals ranged between 1.8% and 22.6% among adults, and 10% and 79% among infants, and was generally more frequent among HIV‐infected compared with HIV‐noninfected individuals . CMV DNA in blood was typically detected early in life indicating that CMV infection was most often acquired within the first 12 months of life …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the prevalence of CMV viremia (cut‐off values ranging from 50 to 200 copies/mL) in different populations with no reported CMV disease symptoms. Detectable CMV DNA in blood in HIV‐infected individuals ranged between 1.8% and 22.6% among adults, and 10% and 79% among infants, and was generally more frequent among HIV‐infected compared with HIV‐noninfected individuals . CMV DNA in blood was typically detected early in life indicating that CMV infection was most often acquired within the first 12 months of life …”
Section: Resultsmentioning
confidence: 99%
“…Congenital and neonatal CMV infections are well‐known threats to children's health and can be associated with severe developmental impairments. A study by Tembo et al identified HIV infection, underweight, and suspected meningitis at admission as potential risk factors for CMV infection in 303 Zambian children (35% HIV+). Furthermore, they observed a significant decrease in the odds for CMV viremia with age.…”
Section: Resultsmentioning
confidence: 99%
“…Third, we were not able to perform typing on all swabs to distinguish HSV-1 from 2 or HHV-6A from 6B; however, the majority of oral shedding of these viruses is due to HSV-1 and HHV-6B 3,27,28 .…”
Section: Discussionmentioning
confidence: 97%
“…Primary infections with HHV-6A have been reported much less frequently, and it is generally assumed that HHV-6A is acquired after HHV-6B, through an asymptomatic infection. However, symptomatic primary infections with HHV-6A have been described for children in the United States as well as in sub-Saharan Africa (154)(155)(156).…”
Section: Clinical Impacts Of Hhv-6 Infections Primary Infectionsmentioning
confidence: 99%